Influence of solvent on the antioxidant and antimicrobial properties of walnut (Juglans regia L.) green husk extracts - Fernández-Agulló, Adela (2016)
Walnut green husk is an agro-forest waste generated in the walnut (Juglans regia L.) harvest that could be valued as a source of natural compounds with antioxidant and antimicrobial properties. At this respect, the effect of the solvent (water, methanol, ethanol and 50% aqueous solutions of methanol and ethanol) on the extraction yields and extracts bioactive properties was analysed. Total phenols content of the extracts was determined by the Folin–Ciocalteau method. Extract antioxidant activity was evaluated using the reducing power assay and by the ability of the extracts to scavenge the DPPH radical. The scavenging effect of the aqueous extracts on the nitric oxide radical was also evaluated. The highest extraction yield was achieved with water (44.11%) and high bioactive potential was shown by the samples extracted with water/ethanol (1:1) (84.46 mg GAE/g extract; EC50 = 0.95 mg/mL for reducing power and EC50 = 0.33 mg/mL for DPPH assay). All the antioxidant properties analysed showed a concentrationdependent activity. The antimicrobial activity of the aqueous extracts was assessed and showed ability to inhibit the growth of Gram positive bacteria. The results obtained demonstrated the potential of the walnut green husk as an economical source of antioxidant and antimicrobial agents.